Clinical assessment of osteoarthritis of the knee. Issue 10 (October 1990) - Cushnaghan, J; Cooper, C; Dieppe, P; Kirwan, J; McAlindon, T; McCrae, F
Abstract : The repeatability of physical signs used to assess osteoarthritis of the knee has not been systematically examined. The within and between observer variation of 10 commonly used physical signs to determine osteoarthritis of the knee has been assessed here. The results obtained show variation in the repeatability of these signs. For those examining the tibiofemoral joints the repeatability was greater than for those examining the patellofemoral joint. It would therefore seem vital to take note of the repeatability of physical signs in determining the number of subjects to be studied in epidemiological studies and therapeutic studies in osteoarthritis.